Ludvig Holbergs religionssyn som udtrykt i "Niels Klim" - Sand, Erik Reenberg (Religionsvidenskabeligt Tidsskrift, 1994)
Niels Klim originally appeared in Latin in 1741 and belongs to the type of literature sometimes called the imaginary travel account. It is shown how this novel, like most contemporary imaginary travel accounts, like Swift's Gulliver's Travels and Montesquieu's Lettres Persanes, was a means of social and religious satire without confronting the censorship which was pretty heavy in Denmark, which at the time was under the sway of German pietism. Holberg's own ideals about society and religion are primarily expressed thrugh the description of the subterranean country of Potu (probably a pun on More's Utopia), an analysis of which shows that his ideal religion was primarily rational and moral, and came pretty close to the contemporary concept of "natural religion", except for his emphatic adherence to the idea of Revelation.